Videolaryngoscope‐assisted flexible intubation tracheal tube exchange in a patient with a difficult airway. Issue 1 (11th April 2019) - Saunders, T. G.; Gibbins, M. L.; Seller, C. A.; Kelly, F. E.; Cook, T. M.
Summary: An 88‐year‐old woman presented with acute airway obstruction caused by a large retrothyroid bleed following anterior neck trauma. Her airway was secured in the operating theatre with an awake nasal flexible optical bronchoscope tracheal intubation using an Intubating Laryngeal Mask Airway tracheal tube. Haemostasis was achieved following surgical ligation and the patient was transferred to the critical care unit. Postoperatively, a large leak around the tracheal tube was noted and a decision was made to change to an orotracheal tube with a subglottic drainage port. Our exchange technique required two experienced operators. The first operator used videolaryngoscopy with a hyperangulated blade to establish an optimal view of the larynx. The second operator placed an airway exchange catheter through the existing nasal tracheal tube to ensure airway control. The trachea was then intubated orally using a flexible optical bronchoscope observed under direct vision using the videolaryngoscope. The technique combined several simple and well‐documented approaches, but importantly, the airway remained secure and visible throughout the procedure.